A non-equilibrium thermodynamic model for tumor extracellular matrix with enzymatic degradation. (July 2017) - Xue, Shi-Lei; Li, Bo; Feng, Xi-Qiao; Gao, Huajian
Highlights: Non-equilibrium thermodynamics for studying chemomechanics of tumor extracellular matrix (ECM). ECM is modeled as a poroelastic polyelectrolyte consisting of a collagen network and proteoglycans. Effects of mechanosensitive enzymatic degradation on drug transport in tumor. ECM degradation modifies tumor microenvironment for improved efficacy of therapy. Abstract: The extracellular matrix (ECM) of a solid tumor not only affords scaffolding to support tumor architecture and integrity but also plays an essential role in tumor growth, invasion, metastasis, and therapeutics. In this paper, a non-equilibrium thermodynamic theory is established to study the chemo-mechanical behaviors of tumor ECM, which is modeled as a poroelastic polyelectrolyte consisting of a collagen network and proteoglycans. By using the principle of maximum energy dissipation rate, we deduce a set of governing equations for drug transport and mechanosensitive enzymatic degradation in ECM. The results reveal that osmosis is primarily responsible for the compression resistance of ECM. It is suggested that a well-designed ECM degradation can effectively modify the tumor microenvironment for improved efficiency of cancer therapy. The theoretical predictions show a good agreement with relevant experimental observations. This study aimed to deepen our understanding of tumor ECM may be conducive to novel anticancer strategies. Graphical abstract: A non-equilibrium thermodynamic theory is established to study the chemo-mechanical behaviors of tumor ECM, which is modeled as a poroelastic polyelectrolyte consisting of a collagen network and proteoglycans.